IMPLEMENTATION OF HOME MONITORING SYSTEM USING LABVIEW FOR CHF - KISHOR RAMNATH GAWANDE; S.N.GAIKWAD (International Journal of Innovations in Engineering Research and Technology, 2021)
Heart failure has found one of severecause of hospitalization.The charges for hospitalization are high and most of the times it has be observed once the patient has got discharge from the hospital, they avoid taking care of themselves.It has observed that the patients are increasingcontinuously for this disease due to the changed life style.After getting discharge from hospital it is costly to arrange the periodic visits of doctors to home.The continuous and unavoidable care is the need of such patients. Hence it is necessary to develop the system which is closely observing the health of the person and tracking the needs of the patient.Authors have proposed the system with the help of Labview to address this problem. The application of the Labviewfor the automatic home monitoringwas implemented by the researchers previously. Authors are trying to implement the same environment for the monitoring of human.Remote monitoring will be one of the best ways to handle the patients in serious diseases without trouble.